A Nice Tailwind: The EU’s Goal Achievement at the IMO Initial Strategy - Earsom, Joseph (2021)
In April 2018, the International Maritime Organization (IMO) reached agreement on its Initial Strategy to reduce greenhouse gas emissions from international shipping. The Initial Strategy was a success for the EU, as it achieved its long-term objective of reaching an international agreement on greening shipping. However, several factors call into question whether the “success” was the result of the role played by the EU. Using process-tracing, we provide insight into the factors and the mechanism that led the EU to achieve its objective with the Initial Strategy. The article finds that the EU’s goal achievement was the result of a mechanism triggered by (1) its overarching objective for action in the IMO on emissions in international shipping; (2) an entrepreneurial coalition partner; and (3) mounting momentum for action in the IMO. While the EU, including through its member states, played an important role in the negotiations, it only did so relatively late in the process, building on the successful work of the Shipping High Ambition Coalition. Based on this case study, we note implications not only for the proposed aspects of the European Green Deal related to greenhouse gas emissions from shipping, but also our understanding of the EU as an international (climate) actor.